Blue rubber bleb nevus syndrome: A rare cause of chronic gastro intestinal bleed in children - Saxena, Sufla; Batra, Himanshu; Taneja, Vikas (Indian Journal of Child Health, 2021)
Blue rubber bleb nevus syndrome (BRBNS) is a rare congenital disorder presenting with multifocal venous malformations of the skin, soft tissues, and gastrointestinal (GI) tract. Here, we report a case of a 10-year-old girl who presented with recurrent lower GI bleeding and abdominal pain requiring repeated blood transfusion for 2 years. A contrast computed tomography showed multiple cavernous haemangiomas in the liver, oesophagogastroduodenoscopy and colonoscopy showed multiple hemangiomas from esophagus to large bowel. Her molecular pathology confirmed BRBNS. She underwent endoscopic argon plasma coagulation with uneventful recovery. In spite of a wide range of therapeutic options for the management of BRBNS described in the literature, the efficacy of those available therapies, including surgical excision, is not well established.